2013
DOI: 10.1007/978-1-62703-363-3_20
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Human Cadaveric Pancreatic Islets for Clinical Transplantation

Abstract: Diabetes is a debilitating condition which can lead to chronic vascular, renal, and ophthalmic disease. Type I or Juvenile Diabetes is caused by the destruction of beta cells within the islets of Langerhans within the pancreas. The beta cells are able to maintain tight control of blood glucose levels by virtue of their ability to secrete insulin in response to small increases in blood glucose concentration. In the absence of beta cells patients with Type I diabetes are dependent on the exogenous administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In early animal and human studies, it was shown that the transplantation of allogeneic pancreatic islets into the liver via the portal vein, coupled with low-dose immunosuppression, could lead to insulin independence and tight blood glucose control. 7 Since these seminal studies, it has been clinically demonstrated that islets isolated from cadaveric pancreases and transplanted into the portal vein of immunosuppressed patients can maintain a state of insulin independence for at least 5 years. [7][8][9][10][11][12] This procedure, however, is still considered an experimental treatment by the Food and Drug Administration (FDA).…”
Section: Pancreatic Islet Autotransplantation For Nonmalignant and Mamentioning
confidence: 99%
See 2 more Smart Citations
“…In early animal and human studies, it was shown that the transplantation of allogeneic pancreatic islets into the liver via the portal vein, coupled with low-dose immunosuppression, could lead to insulin independence and tight blood glucose control. 7 Since these seminal studies, it has been clinically demonstrated that islets isolated from cadaveric pancreases and transplanted into the portal vein of immunosuppressed patients can maintain a state of insulin independence for at least 5 years. [7][8][9][10][11][12] This procedure, however, is still considered an experimental treatment by the Food and Drug Administration (FDA).…”
Section: Pancreatic Islet Autotransplantation For Nonmalignant and Mamentioning
confidence: 99%
“…7 Since these seminal studies, it has been clinically demonstrated that islets isolated from cadaveric pancreases and transplanted into the portal vein of immunosuppressed patients can maintain a state of insulin independence for at least 5 years. [7][8][9][10][11][12] This procedure, however, is still considered an experimental treatment by the Food and Drug Administration (FDA). Islet allografts fail primarily due to inflammatory destruction and immune rejection.…”
Section: Pancreatic Islet Autotransplantation For Nonmalignant and Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Although ample amount of success has taken place regarding the clinical transplantation of cadaveric islets into the liver, which could reverse diabetes (Halberstadt et al 2013), the source of islets from the PSC source has yet to be in the clinics. Enhanced plasticity of PSCs has given greater hopes for the generation of β-cells.…”
Section: Pluripotent Stem Cells For Cell Therapy For Diabetesmentioning
confidence: 99%
“…Considering the purification procedure, incubation of all post-digest pancreas tissue in University of Wisconsin preservation (UW) or similar solutions for a half hour or more is standard practice (11,13,14). Islet purification using high osmolality density gradients also has been adopted by most centers (4, 15Y17) although near isoosmolar alternatives are available (14,18,19).…”
mentioning
confidence: 99%